Regulating Solvation Structure in Nonflammable Amide‐Based Electrolytes for Long‐Cycling and Safe Lithium Metal Batteries - Zhang, Qian‐Kui; Zhang, Xue‐Qiang; Hou, Li‐Peng; Sun, Shu‐Yu; Zhan, Ying‐Xin; Liang, Jia‐Lin; Zhang, Fang‐Shu; Feng, Xu‐Ning; Li, Bo‐Quan; Huang, Jia‐Qi (Advanced energy materials, 2022)
The cycling stability of lithium metal batteries is steadily improving. The safety issues, which mainly result from the employment of flammable solvents, should be strongly considered for practical Li metal batteries. Nonflammable solvents can mitigate fire hazards; however, their employment irreversibly deteriorates the cycling stability of working batteries owing to intrinsic high reactivity against Li metal. Herein, regulating solvation structure in a dimethylacetamide (DMAC)‐based electrolyte is proposed to achieve compatibility between cycling stability and nonflammability of electrolytes. DMAC, a nonflammable solvent, is employed to construct a nonflammable localized high‐concentration electrolyte (LHCE). In the DMAC‐based LHCE, there are abundant aggregate clusters resulting in the formation of anion‐derived solid electrolyte interphase to circumvent parasitic reactions between DMAC solvents and Li metal and to improve the uniformity of Li deposition, which ensures the compatibility between cycling stability under practical conditions and nonflammability of electrolytes. This work opens an emerging avenue to construct long‐cycling and safe Li metal batteries by manipulating solvation structure in nonflammable electrolytes. Regulating solvation structure in a dimethylacetamide‐based nonflammable electrolyte is explored to achieve compatibility between cycling stability and safety of electrolytes for practical lithium metal batteries. In the localized high‐concentration electrolyte, aggregate clusters are generated and result in the formation of an anion‐derived solid electrolyte interphase, and also improve the uniformity of Li deposition.